2020
DOI: 10.3389/fphar.2020.00656
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in NAMPT Inhibitors: A Novel Immunotherapic Strategy

Abstract: Nicotinamide adenine dinucleotide (NAD) is a cofactor of many enzymatic reactions as well as being a substrate for a number of NAD-consuming enzymes (e.g., PARPS, sirtuins, etc). NAD can be synthesized de novo starting from tryptophan, nicotinamide, nicotinic acid, or nicotinamide riboside from the diet. On the other hand, the nicotinamide that is liberated by NAD-consuming enzymes can be salvaged to reform NAD. In this former instance, nicotinamide phosphoribosyltransferase (NAMPT) is the bottleneck enzyme. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
114
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(124 citation statements)
references
References 113 publications
1
114
0
1
Order By: Relevance
“…Silencing NAMPT expression sensitizes tumors to chemotherapeutic agents [49] supporting NAMPT as a clinically-relevant therapeutic target. Prior targeting of NAMPT for cancer treatment has been focused on developing agents that inhibit iNAMPT enzymatic activity and regulation of biosynthesis of NAD via a salvage pathway with the synthesis of nicotinamide mononucleotide (NMN) from nicotinamide (NAM) and phosphoribosyl pyrophosphate (PRPP) [ 12 , 50 ]. iNAMPT enzymatic inhibitors (GMX-1776 or CHS-828, APO-866 aka Daporinad or FK866), have been developed as anti-cancer treatment options.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Silencing NAMPT expression sensitizes tumors to chemotherapeutic agents [49] supporting NAMPT as a clinically-relevant therapeutic target. Prior targeting of NAMPT for cancer treatment has been focused on developing agents that inhibit iNAMPT enzymatic activity and regulation of biosynthesis of NAD via a salvage pathway with the synthesis of nicotinamide mononucleotide (NMN) from nicotinamide (NAM) and phosphoribosyl pyrophosphate (PRPP) [ 12 , 50 ]. iNAMPT enzymatic inhibitors (GMX-1776 or CHS-828, APO-866 aka Daporinad or FK866), have been developed as anti-cancer treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…NAMPT-mediated NAD biosynthesis controls the functions of mammalian sirtuin family members, as well as other NAD-consuming enzymes, such as PARPs, in each subcellular compartment, therefore, involving in a variety of critical biological processes, including cell metabolism and stress response [ 8 , 9 ]. In contrast to iNAMPT, we previously have shown that the extracellularly-secreted NAMPT ( eNAMPT) is a key innate immunity regulator and potent damage-associated molecular pattern protein (DAMP) responding to potentially injurious danger signals [10] , [11] , [12] via ligation of Toll-like receptor 4 (TLR4) and activation of this evolutionarily-conserved inflammatory cascade [10] .…”
Section: Introductionmentioning
confidence: 99%
“…NAMPT and NAPRT can be secreted extracellularly (eNAMPT, eNAPRT) as cytokines and damage-associated molecular patterns (DAMPs): eNAMPT is known as pre-B cell colony-enhancing factor or visfatin [ 40 ], acting through the activation of Toll-like receptor 4 (TLR4) [ 41 ]. The enzyme is involved in human inflammation, obesity, diabetes and has been indicated as a target for anticancer and immunotherapy strategy [ 41 ]: moreover, eNAPRT is a biomarker of sepsis and septic shock [ 42 ].…”
Section: Nad + Biosynthetic and Salvage Pathwaymentioning
confidence: 99%
“…They have a specific dependency on either NAMPT or NAPRT, depending on the cancer type [34], and cells treated with inhibitors of either of these two enzymes show enhanced susceptibility to oxidative stress [35][36][37]. Untransformed cells are less sensitive to ROS induction upon NAMPT inhibition, suggesting a therapeutic window that can be used to target a specific vulnerability in cancer cells [38,39]. Moreover, cytotoxicity induced by glucose deprivation is enhanced in cancer cells and is mediated by increased steady-state levels of ROS [40].…”
Section: Metabolism Functions In the Antioxidant Responsementioning
confidence: 99%